Catalytic Oxidation: Identification and Regulation of Active Sites on Nanodiamonds: Establishing a Highly Efficient Catalytic System for Oxidation of Organic Contaminants (Adv. Funct. Mater. 13/2018). (29th March 2018) - Shao, Penghui; Tian, Jiayu; Yang, Feng; Duan, Xiaoguang; Gao, Shanshan; Shi, Wenxin; Luo, Xubiao; Cui, Fuyi; Luo, Shenglian; Wang, Shaobin
Abstract : Nanodiamonds formed by sp 3 ‐hybridized carbon atoms exhibit great potentials as green catalysts for remediation of organic contaminants. However, the specific active site and corresponding oxidative mechanism are unclear, retarding further developments of high‐performance catalysts. In article number1705295, Jiayu Tian, Xubiao Luo, and co‐workers conclusively determine ketonic carbonyl groups on nanodiamonds as active sites, which can catalyze peroxymonosulfate dissolution into singlet oxygen with high selectivity. The singlet oxygen‐mediated oxidation system significantly outperforms the classical radicals‐based oxidation system in the remediation of organic contaminants in an actual water body.